Analysis of Decisions Determining the Imposition of Black List SanctiONS (Study of Decision 80/G/2022/PTUN.MKS) - Sindawa, Sindawa (UNES Law Review, 2023)
This research aims to determine and analyze the validity of Decision Number: 27/KPTS/Cb29.5/2022 through Decision Number 80/G/2022/PTUN.MKS regarding the imposition of blacklist sanctions in the procurement of goods and services . This research uses normative legal research methods. The use of normative research methods in this research effort is based on the suitability of theory with the research methods required by the author. The results obtained are presented descriptively. The object of the dispute issued by LKPP is proven to contain a juridical defect in the substantive aspect, therefore, because the State Administrative Decree issued by a State Administrative Body or Official must not contain a juridical defect from the element of statutory regulations either from the sub-aspects of authority, formal procedural , or substantial, if it contains a juridical flaw in one aspect, then the State Administrative Decree must be declared null and void, so that there is sufficient legal grounds for the Panel of Judges to grant the Plaintiff's claim.